Synthesis of Polyurethane from Diphenyl Methane 4,4 Diisocyanate (Mdi) Polymerization with Hydroxilated Avocado Oil Polyol - Sihotang, Herlince (Journal of Chemical Natural Resources, 2019)
Polymerization between polyol and isocyanate compounds produces polyurethane in different forms. Polyol used in this study utilized spoiled avocado as the oil source for polyol to produce polyurethane. Avocado oil was epoxidized with formic acid (HCOOH) and H2SO4 catalyst at 40 – 45oC followed by hydrolysis reaction to produce polyol reaction. Next polyol was purified and structure confirmation was done using FT-IR spectroscopy analysis. Polyol was then reacted with diphenylmethane 4,4 diisocyanate (MDI) with ratios of (polyol : MDI) 9:1; 8:2; 7:3; 6:4; and 5:5 (v/v) in a total volume of 10 mL with open air stirring at 40 – 45oC to produce polyurethane. Characterization for the form was observed visually followed by the determination of gel content, density and structure using FT-IR spectroscopy. The results of polyol from avocado oil reacted with diphenylmethane 4,4 diisocyanate for each of the mixing ratio to produce polyurethane is gel content of 74.63% to 99.80% where the higher MDI ratio is, the higher gel content becomes. Density determination from the polyurethane produced is between 0.1341 g/cm3 to 0.7220 g/cm3. FT-IR spectrometer analysis to polyurethane produced is marked with the peaks at 3400 – 3300 cm-1, 2270 – 1940 cm-1, 1700-1600 cm-1 and 1590 – 1540 cm-1 wavelengths which are the characteristic of urethane functional groups.